2020
DOI: 10.3390/pr8121635
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Modification of Unsaturated Polyester Resins to Obtain Hydro- and Icephobic Properties

Abstract: Ice accumulation is a key and unsolved problem for many composite structures with polymer matrices, e.g., wind turbines and airplanes. One of the solutions to avoid icing is to use anti-icing coatings. In recent years, the influence of hydrophobicity of a surface on its icephobic properties has been studied. This solution is based on the idea that a material with poor wettability maximally reduces the contact time between a cooled drop of water and the surface, consequently prevents the formation of ice, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The fabrication method of samples containing MFSC was presented in a previous paper [ 36 ]. The only difference is the type of polymer gelcoat matrix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fabrication method of samples containing MFSC was presented in a previous paper [ 36 ]. The only difference is the type of polymer gelcoat matrix.…”
Section: Methodsmentioning
confidence: 99%
“…These coatings, with low post-surface energy, have been studied for years for minimizing ice deposition [ 32 , 33 , 34 , 35 ]. Kozera et al in 2020 [ 36 ] showed that the chemical modification of a gelcoat based on unsaturated polyester resin with compounds from the MFSC group (triple functionalized polyhedral oligomeric silsesquioxanes (POSS) and double organofunctionalized polysiloxanes) enables one to significantly increase the surface wetting angle and reduce the adhesion to ice compared to the unmodified resin. Linear polysiloxanes (also called oligosiloxanes, depending on the number of structural units) have a chain structure composed of D units, where the inert group is usually the methyl group -OSiMe 2 O- (the most popular poly(dimethylsiloxane), PDMS) or, less commonly, the phenyl group, and terminated groups of type T (usually -OSiMe 3 ) containing both inert and functional building units in the chain structure [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most dominant theory is that superhydrophobic surface with high water repellence exhibit improved anti-icing properties. Due to their potent ability to delay and/or reduce ice accumulation, snow, and frost, they are reported as coatings with high ice phobic potential [31][32][33][34][35][36]. Among many publications, several authors highlighted the effect of contact angle hysteresis on the ice adhesion strength [18,[31][32][33]36], while others have reported reduced ice adhesion for high water contact angle values [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, passive anti-icing materials have been developed greatly, and multitudinous surface materials and approaches were widely used in the anti-icing field. Inspired by Nepenthes pitcher plants, a slippery liquid-infused porous surface (SLIPS) was built and achieved an ultralow ice adhesion strength (0.15–15 kPa). To solve the migration, evaporation, or leakage of infused liquids on SLIPS, a regenerable sacrificial alkane solid organogel surface has been put forward as inspired by the regenerable epicuticular wax on a leaf . The solid-state wax layer could avoid the loss of infused liquid and provide the durable low ice adhesion property.…”
Section: Introductionmentioning
confidence: 99%